Removal of Chromium (VI) cation metal using Poly (N-vinyl-2-pyrrolidone)/Magnetite nanocomposite from aqueous media - G, Padmalaya; BS, Sreeja; S, Radha; G, Raamdheep; J, Saranya (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Groundwater contamination with heavy metals is considered as serious environmental hazard that affect the human society. Nano adsorbents incorporating magnetite nanoparticles provides promising alternative to facilitate removal of heavy metal ions from wastewater. The present work focuses on removal of chromium (VI) cationic metals from aqueous media using Polyvinyl Pyrrolidone (PVP)/Magnetite (Fe3O4) Nanocomposite (MNC). Magnetite nanoparticles are synthesized using chemical co-precipitation and grafted using polyvinyl pyrrolidone to form a magnetite nanocomposite. MNC were characterized with X-ray diffraction (XRD) and Infrared absorption spectrum (FT-IR) studies to affirm the formation and presence of polymeric functional groups of PVP/Magnetite nanocomposite. Batch experiments are carried out at exclusive concentration intervals to study about the adsorption efficiency of MNC on chromium (VI) cationic metal using U-Vis spectroscopy. The results obtained through adsorption studies shows the synthesized PVP/Magnetite nanocomposites has a removal efficiency of 94%.